Zero CO2 steelmaking in a future low carbon economy. 2. Secondary steelmaking using refined iron slab, with clean and contaminated scrap. Issue 2 (3rd April 2018) - Warner, Noel A.
ABSTRACT: Use of an electric arc furnace (EAF) with graphite electrodes is incompatible with zero CO2 emission. EAF usage is challenged by proposed new technology employing generic melt circulation, in which no plant-site carbon dioxide is emitted during scrap melting and subsequent continuous refining. The electrical input is estimated to be less than 150 kWh t −1 for processing shredded scrap to near net-shape product. For continuous steelmaking from contaminated scrap, zinc elimination at atmospheric pressure is straightforward. For copper and tin desorption from contaminated molten steel scrap, continuous, evaporation under vacuum, paralleling the commercially established vacuum dezincing of the molten lead carrier medium in the melt circulation loop attached to the condenser of the former zinc–lead blast furnace at Swansea Vale in the UK, is strongly advocated. A case is made for water cooling in final steel product continuous casting to be replaced by heat recovery employing a liquid metal coolant.